2018
DOI: 10.1002/jbm.a.36322
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linkable graphene oxide embedded nanocomposite hydrogel with enhanced mechanics and cytocompatibility for tissue engineering

Abstract: Graphene oxide (GO) is an attractive material that can be utilized to enhance the modulus and conductivities of substrates and hydrogels. To covalently cross-link graphene oxide sheets into hydrogels, abundant cross-linkable double bonds were introduced to synthesize the graphene-oxide-tris-acrylate sheet (GO-TrisA). Polyacrylamide (PAM) nanocomposite hydrogels were then fabricated with inherent covalently and permanently cross-linked GO-TrisA sheets. Results showed that the covalently cross-linked GO-TrisA/PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…GO nanosheets were oxidized and exfoliated from natural graphite (∼150 μm flakes, Sigma-Aldrich, Milwaukee, WI) through improved Hummers’ method. , Briefly, graphite flakes (3 g) and KMnO 4 (18 g) were added into concentrated H 2 SO 4 /H 3 PO 4 (360 mL/40 mL) under vigorous stirring. The components were reacted at 50 °C under constant stirring for 12 h and then transferred into a glass beaker filled with ice and 3 mL of 30% H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…GO nanosheets were oxidized and exfoliated from natural graphite (∼150 μm flakes, Sigma-Aldrich, Milwaukee, WI) through improved Hummers’ method. , Briefly, graphite flakes (3 g) and KMnO 4 (18 g) were added into concentrated H 2 SO 4 /H 3 PO 4 (360 mL/40 mL) under vigorous stirring. The components were reacted at 50 °C under constant stirring for 12 h and then transferred into a glass beaker filled with ice and 3 mL of 30% H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the functionalization of GDs could also significantly influence the reinforcing effect mainly from two aspects, one of which was that enhanced binding between GDs and matrix might be achieved after the functionalizations, 81,82 and the other of which was that appropriate functionalizations could improve dispersion of GDs in the matrix, thereby getting better structural uniformity. 83,84 For example, Ionita et al 81 prepared porous polyvinyl alcohol Gel-polyvinyl alcohol (Gel-PVA) /GO materials for bone repair by freeze-drying method. Their subsequent results showed that addition of the GO could enhance the compressive strength of the material by 100%.…”
Section: Outstanding Mechanical Propertiesmentioning
confidence: 99%
“…Furthermore, the hydrogel is not easily destroyed at high temperatures and has high stability, and its biocompatibility is improved compared to PAM hydrogels. 68 7.2. Carboxymethyl Chitosan/Graphene Oxide/Polyacrylamide Nanocomposite Hydrogel.…”
Section: Some High-performance Hydrogelmentioning
confidence: 99%